2021
DOI: 10.1080/14737167.2021.1895755
|View full text |Cite
|
Sign up to set email alerts
|

Early economic evaluation of an intervention to improve uptake of the NHS England Diabetes Prevention Programme

Abstract: Background: Despite reported increases in referral numbers, a large proportion of those with prediabetes still decline participation in the NHS England Diabetes Prevention Programme (NDPP). The aim of this study was to explore whether investment in interventions to improve uptake of the programme has the potential to be cost-effective. Methods: An early cost-utility analysis was conducted using a Markov model parameterized based on secondary data sources. We explored different uptake scenarios and the impact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…These reviews identified the following modelling studies with a UK focus: Palmer et al [ 21 ], Gillies et al [ 48 ], Gillett et al [ 49 ] and Breeze et al [ 41 ]. Since these reviews were conducted, there have also been three more modelling studies focusing on the UK setting: Roberts et al [ 18 ], Leal et al [ 34 ] and Frempong et al [ 19 ]. The majority of these studies estimated that prevention programmes of type 2 diabetes are cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…These reviews identified the following modelling studies with a UK focus: Palmer et al [ 21 ], Gillies et al [ 48 ], Gillett et al [ 49 ] and Breeze et al [ 41 ]. Since these reviews were conducted, there have also been three more modelling studies focusing on the UK setting: Roberts et al [ 18 ], Leal et al [ 34 ] and Frempong et al [ 19 ]. The majority of these studies estimated that prevention programmes of type 2 diabetes are cost-effective.…”
Section: Discussionmentioning
confidence: 99%